PEMBIASAAN MEMBACA ASMAUL HUSNA DENGAN METODE SAMBUNG NADHOM DALAM MENINGKATKAN INTERAKSI SOSIAL ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH INKLUSI SDN GROBOGAN 02 JIWAN MADIUN - Permatasari, Intan; Nursalim, Mochamad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effectiveness of the habit of reading Asmaul Husna using the sambung nadhom method in improving social interaction of children with special needs (ABK) in inclusive schools at SDN Grobogan 02, Jiwan Madiun Social interaction is an important aspect for ABK to be able to adapt better in an inclusive school environment. Through the sambung nadhom method, children not only learn to mention Asmaul Husna, but also develop their social interaction skills through a continuous and collaborative learning process. This study used a classroom action research method that involved a series of learning cycles to observe changes in the social interaction skills of ABK. The results showed that the sambung nadhom method in the habit of reading Asmaul Husna significantly increased the self-confidence and social interaction skills of ABK in an inclusive environment. The application of this method has proven effective in building positive interactions between students, increasing empathy, and strengthening communication skills. This article offers practical insights for educators in developing methods that combine religious values ​​and social skills for ABK in inclusive schools.